THE EFFECT OF PROMOTIONAL MIX, TRUST, AND EXPERIENTIAL MARKETING TOWARDS CUSTOMER LOYALTY OF AN ONLINE STORE (A Study on Customers of Blossom Multimedia in Malang) - Alexius Christian Setiawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2020)
This research aimed to determine the influence of the promotion mix, trust, experiential marketing on Online Store customer’s loyalty in Malang. In today’s highly competitive market, retaining customers and maintaining their loyalty is crucial for a business. Looking for a marketing strategy that is suitable for increasing customers loyalty is the obligation of companies. The purpose of this research was to analyze the influence of the promotion mix, trust, and experiential marketing, on customer loyalty of an Online Store in Malang. This research adopted a quantitative approach using 5-point Likert scale online questionnaires. Respondents in this research were millennials generation with ages between 19-37 years, domiciled in Malang, using applications of their own volition, and using applications to order product online. Samples were taken as many as 101 respondents from Blossom Multimedia customers in Malang. Analyzed using Multiple Linear Regression Analysis, results indicated a positive and significant influence of promotion mix, trust, and experiential marketing on customer loyalty.Keywords: Promotion Mix, Experiential Marketing , Trust, Customer Loyalty